Characterisation and analysis of defects on laser powder bed fusion manufactured high-temperature aluminium alloy - Lee, Nicholas Qi Long (Nanyang Technological University, 2023)
Additive Manufacturing (AM), which includes Laser Powder Bed Fusion (L-PBF), has emerged as a sophisticated technology that possesses the ability to create distinct microstructures and expand the possibilities of product design. However, the advancement in product design improvements has outpaced the development of new alloys for metal L-PBF. The commonly used Fe-, Al-, and Ni-based alloys in L-PBF are generally drawn from their well-established cast or wrought forms. However, their integration into the L-PBF process has been carried out with limited knowledge of their processing and adaptability. In addition, it is worth noting that there is a significant lack of research endeavours focused on the development of novel alloys that challenge conventional metallurgical methodologies. This is particularly surprising considering the availability of advanced computational tools that have the potential to greatly aid such progress. L-PBF is a widely utilised additive manufacturing process that is applied to produce intricate and high-performance components. The alloy designated as Al-8.5Fe-1.3V-1.7Si (wt.%) and commonly referred to as Aluminium 8009, is renowned for its remarkable thermal stability and mechanical characteristics, rendering it a highly sought-after substance in the field of advanced engineering. Nevertheless, components produced with the L-PBF technique from this alloy frequently display a range of flaws that undermine their overall usefulness.